Change Management in Public Organizations in Kosovo - Dervishaj, Shefqet Zeqir (European Journal of Multidisciplinary Studies, 2016)
One of the most difficult processes of Kosovo's postwar is the transformation of public organizations. These organizations have undergone radical changes and the process of transformation should be managed in order to be successful and to meet the needs of the market economy. Change has become a constant process for Kosovo public organizations that provide services to citizens and business organizations. Whether these changes are managed properly, then it is seen as a basis for a better performance of public organizations. Kosova after 1999 has undergone major changes in the social, economical, and political systems. Having this situation, public organizations have a great responsibility to the citizens and business organizations to provide services to adapt to the global trend of development and from which Kosova has been isolated. In this paper the focus will be on the impact of factors that affect the change process; how the process of change is developed; what are the barriers/obstacles that hinder the process of change; what are the benefits of the change; how much are managers in public organizations qualified to implement the process of change. Based on data collected from the field and from current practices, I will make their comparisons and draw conclusions about what factors influences the management changes and what are the barriers that will affect to increase efficiency and effectiveness in the organization gained from the data obtained in study. The data will be collected through questionnaires and findings obtained will help to come into a conclusion that these factors act as change management in public organizations in Kosovo.
Keywords: management of change, barriers, public organizations